2010
DOI: 10.4314/swj.v5i1.61481
|View full text |Cite
|
Sign up to set email alerts
|

Foliar epidermal and phytochemical studies of the grasses <i>Cymbopogon citratus</i> (stapf.), <i>Axonopus compressus</i> (P. Beauv.) and <i>Eragrostis tremula</i> (S. W. Beauv) in Ekpoma, Edo state, Nigeria.

Abstract: This study presents investigations into the epidermal and phytochemical features of Eragrostis tremula (S.W.Beauv.), Cymbopogon citratus (Stapf.) and Axonopus compressus.(P.Beauv.). Epidermal features of the different species in the three genera showed slight differences for both the adaxial and abaxial parts with respect to prickles, papillae, macro hairs and micro hairs. Long cells, short cells, stomata and silica bodies are almost universally present in all the three species. With respect to their phytochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Therefore, current study focused on their taxonomic identification with the help of leaf epidermal characteristics. The leaf epidermal characters have provided information of taxonomic importance (Ogie‐Odia, Eseigbe, Ipechie, Erhabor, & Ogbeboy, 2010). Foliar epidermal characters have significance in plant systematics and characterization of subfamilies and tribes (Brown, 2008; Watson & Dallwitz, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, current study focused on their taxonomic identification with the help of leaf epidermal characteristics. The leaf epidermal characters have provided information of taxonomic importance (Ogie‐Odia, Eseigbe, Ipechie, Erhabor, & Ogbeboy, 2010). Foliar epidermal characters have significance in plant systematics and characterization of subfamilies and tribes (Brown, 2008; Watson & Dallwitz, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the observed mineral content varies with different methods of sample preparation and testing. Ogie-Odia et al (2010) studied the epidermal and phytochemical features of lemon grass using a scanning electron microscope. The micrograph showed the presence of silica bodies, mostly in a cross shape on the adaxial surface of the lemon grass.…”
Section: Introductionmentioning
confidence: 99%
“…have been reported to demonstrate antidiabetic activities (Suba et al, 2004) also previous studies have shown that Axonopus compressus contains all the above phytoconstituents (Ogie-Odia et al, 2010). It is therefore possible that the phytochemicals present in the plant may be responsible for the observed antidiabetic activity.…”
Section: Discussionmentioning
confidence: 94%